Residual crisis and challenges for the 21st century of Chilean secondary education: debates and dilemmas - RONDÓN MEJÍAS, Bárbara; DONOSO DÍAZ, Sebastián (Utopía y Praxis Latinoamericana, 2023)
High school education represents a transcendental stage for personal and social development. For several decades, Chile has promoted adjustment processes in accordance with the prevailing educational demands. This article addresses the transformation processes of Chilean secondary education since the 1960s, with the aim of examining the main difficulties, advances, and challenges, as well as discerning the complex problem that is woven into the social sense construct at this educational stage. Secondary sources were used as a reference, and after the review process, it became evident that despite efforts to modify and adapt high school education to the requirements of the time, academic problems of quality and segmentation persist since the 20th century, which puts their social sense in risk. In this sense, it is imperative to consolidate effective educational policies that allow the development of optimal skills for the 21st century.